Integration of Islamic Values in Character Education: a Case Study at Madrasah Salafiyah - Ikhwan, Afiful (Jurnal Pendidikan Nusantara, 2025)
This study aims to analyse the personality traits of students at Madrasah Salafiyah Ulya Nashrus Sunnah and understand how an educational process that combines the Salafiyah method, memorisation of the Qur'an, and religious understanding can shape students' characters to be disciplined, responsible, and honest. The method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. Data is analysed using three stages: data reduction, data display, and conclusion description/verification. The results of the study show that 95% of students arrive on time for Halaqoh and morning dzikir, reflecting high discipline. Additionally, 90% of students did not engage in academic misconduct, and 100% of students participated in congregational obligatory prayers. Character development was achieved through habit formation, teacher modelling, and collaboration with parents. These findings indicate that character education in this madrasah successfully cultivates individuals who are not only academically intelligent but also possess good moral character. In conclusion, the implementation of an educational method that integrates Islamic values and positive habits significantly contributes to the development of students' character, making them more disciplined, responsible, and honest. This study emphasises the importance of character education in creating a balanced and quality generation, ready to face the challenges of the times with strong religious principles.